2014
DOI: 10.1007/s00383-014-3622-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term expression pattern of melanocyte markers in light- and dark-pigmented dermo-epidermal cultured human skin substitutes

Abstract: Purpose Transplantation of pigmented tissue-engineered human autologous skin substitutes represents a promising procedure to cover skin defects. We have already demonstrated that we can restore the patient's native light or dark skin color by adding melanocytes to our dermo-epidermal skin analogs. In this long-term study, we investigated if melanocytes in our skin substitutes continue to express markers as BCL2, SOX9, and MITF, known to be involved in survival, differentiation, and function of melanocytes. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…We recently demonstrated for MelSkin the regular distribution of melanocytes in the basal layer with the protrusion of dendrites into lower and upper keratinocyte layers and the deposition of supranuclear melanin caps in the keratinocytes (Biedermann et al 2015b).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…We recently demonstrated for MelSkin the regular distribution of melanocytes in the basal layer with the protrusion of dendrites into lower and upper keratinocyte layers and the deposition of supranuclear melanin caps in the keratinocytes (Biedermann et al 2015b).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the original color of the donor skin was restored after transplantation (Biedermann et al 2015b;Böttcher-Haberzeth et al 2013). Distinct MelSkin substitutes differing in color (light or dark) showed physiological melanocyte distribution and function even 15 weeks after transplantation (Biedermann et al 2015a;Böttcher-Haberzeth et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human skin, epidermal melanocytes exist in distinct maturation states. We and others have shown that SOX9 is expressed in a subpopulation of melanocytes and that this correlates with the presence of MelanA þ and PMEL þ mature cells in the epidermis and in the hair matrix of normal (nonpalmoplantar) human skin (Biedermann et al, 2015a;Krahl and Sellheyer et al, 2010). In contrast, SOX10 plays an important role during the early development of melanocytes in the neural crest and is still expressed in immature melanocytes in the epidermis (Greenhill et al, 2011;Harris et al, 2013).…”
Section: Discussionmentioning
confidence: 88%